2016
DOI: 10.18203/2349-3933.ijam20162503
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity C-reactive protein in metabolic syndrome

Abstract: Background: Presence of metabolic syndrome in an individual substantially increases his risk of developing cardiovascular disease and type 2 diabetes mellitus. Occurrence of both obesity and type 2 DM have reached epidemic proportions in India. Metabolic syndrome is considered to be a proinflamatory state associated with low grade systemic inflammation. C-reactive protein is a robust biomarker of this chronic systemic inflammation. Higher values of high sensitivity C-reactive protein (hs-CRP) are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
2
0
3
Order By: Relevance
“…17 In the present study, there was higher mean concentration of hs-CRP in patients with metabolic syndrome (1.5±0.1mg/l v/s 2.2±0.2mg/l V/S 2.1±0.1mg/l) and there was a linear increase in the values with increasing number of components of the metabolic syndrome. These results were in accordance with a study by Gowdaiah PK et al 18 Similar finding was found by Bo S et al 19 Anubha Mahajan et al also had similar results where hs-CRP values were significantly elevated in subjects with metabolic syndrome compared to subjects without metabolic syndrome. 20 This suggests the fact that higher the number of components of metabolic syndrome in a patient, higher the values of hs-CRP and the risk of development of cardiovascular events.…”
Section: Discussionsupporting
confidence: 92%
“…17 In the present study, there was higher mean concentration of hs-CRP in patients with metabolic syndrome (1.5±0.1mg/l v/s 2.2±0.2mg/l V/S 2.1±0.1mg/l) and there was a linear increase in the values with increasing number of components of the metabolic syndrome. These results were in accordance with a study by Gowdaiah PK et al 18 Similar finding was found by Bo S et al 19 Anubha Mahajan et al also had similar results where hs-CRP values were significantly elevated in subjects with metabolic syndrome compared to subjects without metabolic syndrome. 20 This suggests the fact that higher the number of components of metabolic syndrome in a patient, higher the values of hs-CRP and the risk of development of cardiovascular events.…”
Section: Discussionsupporting
confidence: 92%
“…hs-CRP levels less than 1, 1 to 3, and greater than 3 mg/L indicate a low, moderate, and high risk for future CHD events and stroke. In the present study, the baseline hsCRP values were more than 6 mg/L, indicating a very high cardiovascular event risk [27]. As seen from Tables 17 and 18 mean percentage decrease in hsCRP levels by all the groups was significant at almost all treatment periods.…”
Section: Resultssupporting
confidence: 43%
“…Abdominal obesity and insulin resistance have a significant role in MS development 19 . Recent studies have shown that patients with MS have significantly higher levels of high sensitive CRP, compared to the control group, which is a marker of chronic inflammation in patients with MS, whose values increased linearly with the increase number of factors for MS 20 . Obesity is characterized by elevated levels of inflammatory factors such as CRP and prothrombogenic factors such as fibrinogen, which occur before other MS disorders and are useful in the assessment of cardiovascular risk 21 .…”
Section: Discussionmentioning
confidence: 99%